Memori Budaya Sebagai Kritik Ekoteologis: Reaktualisasi Kosmogoni Sauan Sibarrung terhadap Eksploitasi Kerbau di Toraja - Herman Tolan; Riyanti Sattu; Mega Rante Rara (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Buffalo hold a central place in Toraja social-religious life, serving both as sacrificial animals in the Rambu Solo funeral rite and as status symbols in the Ma’pasilaga Tedong buffalo-fighting tradition. Economic interest and social prestige have driven some breeders to administer harmful substances to buffalo to secure contest victories, a practice that disregards animal welfare and contradicts local cosmology. This article examines how sauan sibarrung and sangserekan, concepts holding that humans, animals, and plants originate from the same source of creation, can be reactualized as an ecotheological critique of this exploitative practice. Using a qualitative-ethnographic method through in-depth interviews with traditional and religious leaders and a literature study of Torajan ritual texts, this research finds that the ethical disconnection between humans and buffalo stems from an erosion of cultural memory caused by the dominance of contest-economy logic. Combining Jan Assmann’s cultural memory framework with Lynn White’s ecotheological critique, this article argues that reactualizing sauan sibarrung offers a concrete ethical path forward for Toraja society: buffalo, as kin of humans sharing one origin, should be treated with dignity rather than as mere economic instruments in contests.